ANALISIS KARAKTERISTIK FUNGSI ZEOLIT ALAM AKTIF SEBAGAI KATALIS SETELAH DIIMPREGNASI LOGAM NIKEL - Rina Novia Yanti; Erliza Hambali; Gustan Pari; Ani Suryani (Jurnal Penelitian Hasil Hutan, 2021)
Catalytic cracking is a conversion process by cutting the carbon chains of oil molecules into simple hydrocarbons. The process ofbreaking the hydrocarbon chain could be conducted by chemical means using a catalyst and hydrogen gas. The types of catalystscommonly used in the chemical industry are metals such as nickel (Ni), zinc (Zn), and cadmium (Cd). The metal can be used asa catalyst directly, but during the catalytic cracking process, the catalyst will thicken than it is imposible to re-use the catalyst.Therefore, the metal catalyst must be impregnated into a carrier material such as zeolite. The research is aiming for analyzing thecharacteristics of active natural zeolite catalyst with nickel-metal impregnation (ZAA/Ni), which consisted of surface area analysis,XRD, FTIR, and morphological analysis best catalyst. The zeolite used in this research is originated from Bayah Banten, whichhas been activated. The function of the catalyst can be improved by the presence of a carrier, namely nickel metal. The role of thecarrier is as a place for the active nucleus to spread, which can increase the effectiveness of the catalyst so that the catalyst can beused repeatedly. Results show the highest Si/Al ratio is 6.66, an intermediate catalyst with a Si/Al ratio = 2−10. The widestsurface area of the catalyst is at ZAA/Ni 3% of 974.44 m2/g; the crystallinity value the largest was 70.09%. Zeolite fromBayah Banten, impregnated with nickel-metal, can be used as a catalyst for upgrading bio-oil with a concentration of 3% ZAA/Niand 2% AA/Ni.